EFFECT OF HEALTH EDUCATION WITH AUDIO-VISUAL MEDIA AS COVID-19 PREVENTION ON HANDWASHING BEHAVIOUR IN SCHOOL AGE CHILDREN - Mamesah, Marline; Wijaya, Hermanto (jfpublisher, 2022)
Introduction. Coronavirus Disease 2019 is caused by SARS-Cov-2 which can be transmitted through physical contact such as touching and shaking hands with sufferers. School-age children are at high risk of hand-to-mouth transfer when they come into contact with feces while playing on the school grounds. School is a strategic place and plays a role in optimizing the growth and development of school-age children with promotive and preventive efforts in health. Health education with audio visual will make them imagine and want to try something new, so that through this media it will improve their intellectual and cognitive abilities. This research aim was to analysis effect of health education with audio-visual media as Covid-19 prevention on handwashing behaviour in school age children. Method. This research was Pra-Experiment with one group pretest-posttest design. The number of respondents is 28 students of class V and VI SD Negeri Kapasan 5 Surabaya. Collecting data using observation checklists and questionnaire sheets. Data analysis used the Wilcoxon test with a significance level of 0.05. Results & Analysis. This study showed there was an effect of health education with audio-visual media on the ability (p=0.000<0.05), knowledge (p=0.001<0.05), and handwashing attitude (p=0.001<0.05) in school-age children as Covid-19 prevention. Discussions. School-age children are in an active and imaginative phase. Audio visual media make them more interested in learning, because through the media sound and images are presented to support the learning process. Children also experience good and optimal cognitive, motor and intellectual development.